The influence of balance of payment and fixed Investment on external debt level in South Africa - Molefe, S. B.; Dzivhani, M. P. (International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference, 2020)
Debt remains a key and critical indicator for African countries, from state indebted institutions to state projects funded through external debt. Given that South Africa was recently downgraded, external debt is a contentious issue grappling policy formulation. Hence, the study investigates how balance of payment and internal investment influence external debt level. Quarterly time series data was used from 2004 to 2017 employing Vector Error Correction Model and Granger Causality techniques in the study. VECM results show that fixed investment has a negative and significant predictor of external debt, while balance of payment was an insignificant predictor in the long run. The Granger causality results revealed that fixed investment has a causal effect on external debt significant at 5%, while balance of payment is rather affected by external debt significant at 5% also. It is therefore recommended that the country needs to mobilise and sufficiently make use of internal investments, this will deter excessive external borrowing to fund infrastructure and critical projects. It is also recommended that, perhaps, South African firms need to invest productively abroad, thereby, improving foreign direct investment (an asset value) income, this will contribute to the current account. As such investment will help deter the impact of the negative outlook imposed by ratings agencies on the country. Balance of payment, with the causal effect on debt level, may also help deter the impact of the ratings agencies pronouncements on South Africa. Keywords: Balance of payment, External debt, Fixed Investment, Current account
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Balance of payment; External debt; Fixed Investment; Current account; Debt; Debt, External; Investments